PENENTUAN KESESUAIAN LOKASI BUDIDAYA LOBSTER MENGGUNAKAN APLIKASI SIG DI WILAYAH PESISIR PUNTONDO - Damis, Damis (Jurnal Sains dan Teknologi Perikanan, 2021)
The results of the analysis using GIS software produce a thematic map of land suitability for lobster culture of the Karamba Floating Nets system with the suitability category obtained by adding up the values ​​of all parameters to get the final score so that the values ​​obtained between classes (Ci) are obtained. The Ci value obtained was 0.7 with a maximum Result Score (SHB) score of 3.0 and a minimum value of 0.8. The suitability category is determined based on the range or class interval where the corresponding criteria (S) are in the class interval 1.6 - 3.0 and the criteria does not match (N) based on the SHB interval 0.8 - 1.5. The results of the suitability evaluation conducted in this study are the actual suitability or land suitability, where the resulting land suitability class is only based on available data, not considering social, economic, financial, and other aspects. The results of the land suitability analysis based on the suitability matrix of the merging results for the lobster culture of the KJA system obtained the appropriate criteria (S) of 71.06 ha and not suitable (N) of 89.15 ha.